Monitoring Urbanization Induced Surface Urban Cool Island Formation in a South Asian Megacity: A Case Study of Bengaluru, India (1989–2019) - Sarif, Md. Omar; Ranagalage, Manjula; Gupta, Rajan Dev; Murayama, Yuji (Frontiers in Ecology and Evolution, 2022)
Worldwide many cities have been going through thermal state intensification induced by uncertain growth of impervious land. To address this challenge, one of the mega-cities of south Asia, Bengaluru (India), facing intense urbanization transformation, is taken up for detailed investigations. Three decadal (1989-2019) patterns and magnitude of natural coverage and its influence on the thermal state are studied in this present research for assisting urban planners in adopting the mitigation measures to achieve sustainable development in the mega-city. The main aim of the present research is to monitor surface urban cool island (SUCI) in Bengaluru city, one of the booming megacities in India, is monitored using Landsat data during 1989–2019. This study is further focused on the analysis of land surface temperature (LST), bare surface (BS), impervious surface (IS), and vegetation surface (VS). The SUCI intensity (SUCII) is examined through the LST difference based on the classified categories of land use/land cover (LU/LC) using urban-rural grid zones. In addition, we have proposed a modified approach in the form of ISBS fraction ratio (ISBS–FR) to cater to the state of urbanization. Furthermore, the relationship between LST and ISBS–FR and the magnitude of the ISBS–FR is also analyzed. The rural zone is assumed based on recorded < 10% of the fraction of IS (FIS) along the zones in the urban-rural gradient (URG). It is observed that SUCII hiked by 1.92 ℃ in 1989, 4.61 ℃ in 2004, and 2.66 ℃ in 2019 between demarcated urban and rural zones along URG. Further, the results indicate a high expansion of impervious space in the city from 1989 to 2019. The alteration in the city landscape is mostly occurring due to impervious development, causing the intensification of SUCI. The mean LST (MLST) has a negative relationship with the fraction of VS (FVS) and a positive relationship with the fraction of BS (FBS). In addition, the ISBS–FR shows intense enlargement. The findings of the present study will add to the existing knowledge base and will serve as a road map for urban and landscape planning for environmental enrichment and sustainability of the mega–city of Bengaluru.